International Trade and Health Care in Brazil: An Unpredicted Tale Threatening Health Care Entitlement?. (April 2019) - Santos, Milton; Filippon, Jonathan; Mendes, Áquilas; Kondilis, Elias
The General Agreement on Trade in Services (GATS), established in 1994, has been a key element of market liberalization of health care services. Brazil had the provision of health care services partially protected from international competition until 2015, when a constitutional change opened the national health care market to international provision. We performed a retrospective and prospective policy analysis based on a systematic policy document review, general literature review, and secondary data analysis mapping, describing and analyzing the international trade agreements signed by Brazil with the World Trade Organization (WTO) and the available legislation relevant to health care services. The provision of health care services was not included in the WTO commitments signed by Brazil during the analyzed period (1994–2018). Financing of private health insurance was part of the agreement since 1994. There was a mild liberalization of the private health insurance sector, while provision of health care services was forbidden to foreign investors until 2015. The mode 3 of GATS presents the greatest potential impact as it exposes health care provision to international competition. The international liberalization of the provision of health care services in Brazil is now legal and an observable consequence of the pressure to gradually lift trade barriers in the health and health care sector.